STUDY OF MECHANICAL PROPERTIES OF COMPACTED MATERIALS GROUND PADS AS RANDOM VARIABLES - Vynnykov, Yu. L.; Kharchenko, M. O. (Science and Transport Progress, 2010)
The statistic analysis of variability values of mechanical characteristics of compacted soils is done. Also the laws of their distribution are determined. As a result, it is determined that for the deformation modulus, unit cohesion and internal friction angle the logarithmic normal law of distribution is more correct, while for penetration resistance – exponential law.